2003
DOI: 10.1063/1.1530727
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and 90° domain contribution to ferroelectricity of epitaxial Pb(Zr0.35,Ti0.65)O3 thin films

Abstract: Remanent polarizations (Pr) of 200-nm-thick epitaxial Pb(Zr0.35,Ti0.65)O3 (PZT) thin films deposited on (001), (110), and (111) SrTiO3 (STO) substrates coated with SrRuO3 (SRO) were compared to the domain configurations that were precisely and quantitatively characterized by high-resolution x-ray diffraction reciprocal space mapping (HRXRD-RSM). (001)/(100), (101)/(110), and (111) oriented domains were obtained for films grown on (001), (110), and (111) STO substrates coated with SRO, respectively. HRXRD-RSM s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 16 publications
1
33
0
Order By: Relevance
“…High-resolution XRD reciprocal space mapping 15 ͑HRXRD-RSM͒ was employed to analyze the crystal structure, including the film orientation, in-and out-of-plane lattice parameters, and the interaxial angle in detail. The composition of the film was measured with an x-ray fluorescence ͑XRF͒ spectrometer ͑PANalytical PW-2404͒, which was calibrated using sol-gelderived standard samples and cross-checked by Rutherford backscattering spectrometry ͑RBS͒.…”
Section: Methodsmentioning
confidence: 99%
“…High-resolution XRD reciprocal space mapping 15 ͑HRXRD-RSM͒ was employed to analyze the crystal structure, including the film orientation, in-and out-of-plane lattice parameters, and the interaxial angle in detail. The composition of the film was measured with an x-ray fluorescence ͑XRF͒ spectrometer ͑PANalytical PW-2404͒, which was calibrated using sol-gelderived standard samples and cross-checked by Rutherford backscattering spectrometry ͑RBS͒.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, thin films of Pb(Zr 1-x Ti x )O 3 (PZT) have been fabricated in many laboratories worldwide, and even epitaxial PZT films were grown on many different substrates. [1][2][3][4][5][6][7][8][9][10][11][12][13] The experimental results demonstrated important distinctions between the properties of PZT in a thin-film and bulk forms, which triggered the first theoretical studies of PZT thin films. [14][15][16][17] Two approaches were employed in these studies, namely, the thermodynamic calculations and the phase-field simulations.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Recent experimental work has demonstrated that the control of film orientation is one promising and effective approach to manipulate ferroelectric domain structure and properties. 3,4 In studies of thin-film materials, such as the model ferroelectrics PbZr 1−x Ti x O 3 and BiFeO 3 , it has been noted that the variation of film orientation could result in exotic crystal and domain structures and give rise to enhanced ferroelectric susceptibilities. [5][6][7][8] In particular, recent work on (111)-oriented, tetragonal PbZr 0.2 Ti 0.8 O 3 films highlighted how domain-wall contributions to dielectric susceptibilities and ferroelectric switching characteristics can be dramatically tuned with film orientations.…”
Section: Introductionmentioning
confidence: 99%